Risk factors of increased blood pressure among adolescents in rural areas of Indonesia - Ningsih, Oliva Suyen; Wea, Lidwina Dewiyanti; Handi, Heribertus (Gaceta Médica de Caracas, 2022)
Introduction: Hypertension in adolescents can increase mortality and morbidity rates, affecting productivity decline in adolescents. The prevalence of hypertension in adolescents is increasing and is often not realized by adolescents. This study aimed to identify risk factors for increased blood pressure in adolescents in rural areas. Methods: This study uses a cross-sectional study design carried out in May 2022 in one of the senior high schools in Manggarai Regency, East Nusa Tenggara. The sample in this study was students aged 13-18 years (n=44) based on the inclusion criteria. The sampling technique used was convenience sampling with data analysis using Chi-Square.